Identification of a 23 kDa chloroplast stress protein as a marker for drought tolerance in Hevea brasiliensis - Annamalainathan K; Jacob J; Pramod S; Sumesh K.V (National Conference of Plant Physiology-2016. Challenges in Crop Physiology Research: From Molecular to Whole Plant, 8-10 December 2016, University of Agricultural Sciences, Bengaluru and Indian Society for Plant Physiology, New Delhi, India. Abstracts. p. 22.)
Ten different clones of Hevea brasiliensis were evaluated under soil moisture deficit condition for their relative drought tolerance potential. Physiological parameters such as leaf water potential, photosynthetic oxygen evolution rate of leaf, quantum yield of PSII activity (xPSII) and net CO2 assimilation (A) rate were measured. The clones, RRIM 600, RRII 208 and RRII 430 recorded comparatively small decline in A and comparatively stable PS II activity upon exposure to soil moisture decifit stress. On the other hand, clones PB 260, RRII 105, RRII 414 and RRII 417 were found more susceptible in terms of severe inhibition of photosynthetic activities under moisture stress. Western blot analysis revealed consistent over-expression of a low molecular weight (23 kDa) chloroplast protein in the relatively drought tolerant clones, RRIM 600 and RRII 430. Further, this presence of this stress protein was validated in more number of clones of Hevea. It was observed that exposure to light was a pre-requisite for its over-expression under conditions of moisture stress. Together with other parameters, the relative over-expression of this protein is being used as screening tool for selecting drought tolerant clones of rubber.
Keywords: Drought tolerance; Stress protein